AB0536 Prevalence of inflammatory back pain among workers of a university health sciences campus. (23rd January 2014) - Onen, F.; Solmaz, D.; Cetin, P.; Akar, S.; Akkoc, N.; ,
Abstract : Background: The early identification of IBP may provide early diagnosis of axial spondyloarthritis. However the exact prevalence of inflammatory back pain (IBP) in the general population is not well documented. Objectives: The aim of this study was to determine the prevalence of IBP in the workers of a university campus in Izmir, Turkey. Methods: The study was conducted in the Health Sciences Campus with a population of 2894 workers who aged between 20 years and 67 years, at Dokuz Eylul University in Izmir. A sample size of 395 subjects was calculated by assuming that the IBP prevalence of 5% in the general population using OpenEpi (version 2.3 Atlanta, GA, USA), based on a confidence interval of ±2%. Six trained medical students using a standard questionnaire performed a face-to-face interview with participants. The subjects were classified as having IBP using various criteria including Calin criteria, Berlin criteria and ASAS Experts' criteria. Results: A total of 381 subjects (131 male, 250 female; mean age: 38.0 ± 9.4) were contacted with an acceptance rate of 96.5%. Among them, 299 (78.5 %; CI 95% 74-82) had experienced back pain at least one time in their life. A total of 172 subjects (45.1 %; CI 95% 40-50) had chronic back pain lasting more than a month. Among 381 subjects, 82 (21.5 %; CI 95% 17-25) were classified as having IBP according to Calin Criteria. The prevalence of IBP according to Berlin and ASAS Experts' criteria was found to be 7.0% (CI 95% 4-10) and 6.5% (CI 95% 4-9), respectively (Table ). Among subjects with chronic back pain, the prevalence of IBP was estimated as 43.4 % (CI 95% 36-51), 15.1 % (CI 95% 10-21) and 14.8 % (CI 95% 10-20), based on Calin, Berlin and ASAS Experts' criteria, respectively. Two patients had a previous diagnosis of axial spondyloarthritis. A previous diagnosis of lumbar disc hernia (LDH) was more frequent in subjects classified as having IBP (35.4%) than those classified as not having IBP (p<0.05). Conclusions: This study is still in progression to investigate the prevalence of axial spondyloarthritis in the same population. The present results suggest that IBP is more common than expected in the general adult population. Disclosure of Interest: None Declared